Teologi Pendidikan: Konsep Pendidikan dalam Prespektif Islam - Dewi Fitriani; Nurwadjah Ahmad EQ; Andewi Suhartini (MANAZHIM, 2021)
Theology is an effort to contextualize religious teachings, not just textualizing, to answer human problems, not only problems of faith, monotheism but also cultural problems, problems of daily life, where the problems faced by humans are never-ending. In the context of Islam, the word theology will be more precise and meaningful when it is associated with the word Islam, so that the understanding of theology in question is theology that breathes Islam. An understanding of educational theology, in fact requires the inclusion of the conception of education and or deriving the concept of education in and from the schools of mutakallimin thought. Education is an interaction, namely the process of giving and taking, between humans and the environment. It is a process by which humans develop and create the skills needed to change and improve human conditions and their environment, as well as the formation of attitudes that guide their efforts to rebuild their human and physical characteristics. Education in Islam is often interpreted as At. Tarbiyahi (Education), the meaning is very thick and related to ar-riyadhah (practice). The training in question includes physical and spiritual training. The purpose of Islamic education is the formation of students to become servants of Allah who are pious and responsible for carrying out worldly and ukhrawi work.